GENO PROTECTIVE AND ANTI-APOPTOTIC EFFECT OF GREEN TEA AGAINST PERINATAL LIPOPOLYSACCHARIDE-EXPOSURE INDUCED LIVER TOXICITY IN RAT NEWBORNS - Allam, Ahmed A.; Gabr, Sami A.; Ajarem, Jamaan; Alghadir, Ahmad H.; Sekar, Revathi; Chow, Billy KC (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: This study aims to examine the protective effect of green tea on the disturbances in oxidative stress andapoptosis related factors, mostly produced due to perinatal lipopolysaccharide (LPS) exposure, that subsequentlyinduces liver cell damage.Materials and Methods: Anti-free radical, Antioxidant, scavenging, geno-protective, and antiapoptotic activity ofaqueous green tea extract (AGTE) were assessed against LPS-induced hepatic dysfunction in newborn-rats. AGTE atdoses of 100 & 200 mg/kg was orally administered daily to rat dams, during gestation and lactation.Results: AGTE was observed to exhibit protective effects by significantly attenuating LPS-induced alterations inserum AST, ALT, bilirubin, and albumin levels. Significant increase in the total antioxidant capacity (TAC), DNAcontents, and reduction in nitric oxide (NO) levels were observed in AGTE treated rats comparing LPS-toxicated ones.Additionally, AGTE treatment significantly down-regulated apoptotic markers and this effect was directly correlated tothe degree of hepatic fibrosis. The possible mechanisms of the potential therapeutic-liver protective effect of AGTEcould be due to free radical scavenging potential and antiapoptotic properties caused by the presence of antioxidantpolyphenolic components in AGTE.Conclusion: We thereby propose, based on our findings, that the anti-free radical and anti-apoptotic inducingproperties of AGTE active constituents attribute to its functional efficacy as anti-fibrotic agent.